Strategi Kesantunan Bertutur Mahasiswa Kepada Dosen Melalui Komunikasi WhatsApp - Husna, Liza Lailatul; Arief, Ermawati (Universitas Negeri Padang, 2020)
ABSTRACT This article reveals the politeness strategy for students speaking to lecturers through WhatsApp communication. There are the four purposes of this research. First, describe the student’s speaking strategy to lecturers via WhatsApp communication. Second, describe the principle of politeness to lecturers through WhatsApp. Third, describe the scale of student language politeness. Fourth, describe the politeness of student language to lecturers. The design of this study is qualitative with descriptive method. This research was conducted at the Indonesian Language Education Study Program, Padang State university. The data was collected from two semesters, namely the odd semester of July―Desember 2019 and the even semester of Januari―June 2020. Basedon the results of the study, it can be concluded that the most widely used strategy is the strategy of speaking using negative politeness and student speech can be said to be polite. Kata kunci: Strategi, Kesantunan Bertutur, Mahasiswa kepada Dosen, Komunikasi WhatsApp.